IMPLEMENTASI PROGRAM JEMPUT ANTAR IBU MELAHIRKAN DI PUSKESMAS PERHENTIAN LUAS KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI TAHUN 2018-2023 - Anggara, Sandi; Nasution, Hazqon Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research is motivated by the phenomenon related to the Jemput Antar Ibu Melahirkan (Jamela) program, namely the absence of a team that records pregnant women who want to give birth. There are several village areas that are difficult to reach by ordinary vehicles, in addition to the customary factors of giving birth to traditional birth attendants to preserve local culture. This study uses qualitative research methods, research data obtained by interview techniques. The results of this study are: (1) the implementation of the Jemput Antar Ibu Melahirkan (Jamela) program at the Perhentian Luas Health Center, Logas Tanah Darat District, Kuantan Singingi Regency 2018-2023 has not been implemented optimally, because the aspects of communication and resources have not been implemented optimally. Meanwhile, the aspects of disposition and bureaucratic structure of the implementing party have been implemented; and (2) the factors that become obstacles to the implementation of the Jemput Antar Ibu Melahirkan (Jamela) program at Puskesmas Perhentian Luas, Logas Tanah Darat District, Kuantan Singingi Regency 2018-2023 are consists of internal and external factors. Internal factors come from the puskesmas, such as the absence of adequate vehicles to reach all Puskesmas working areas, the absence of a socialization team from the Puskesmas, lack of number and availability of midwives in following up the Jamela program, and the fact that the midwife on duty is not in place during working hours. While external factors come from the community, namely some people who still entrust the birth process with traditional birth attendants due to local customs and culture, and the lack of public awareness about the importance of giving birth in accredited health facilities. Keywords : Communication, Resources, Disposition, Bureaucratic Structure